Phosphotransferase System-Dependent Extracellular Growth of Listeria monocytogenes Is Regulated by Alternative Sigma Factors σ(L) and σ(H) - Wang, Siyun (Appl Environ Microbiol, 2014)
Alternative sigma (σ) factors and phosphotransferase systems (PTSs) play pivotal roles in the environmental adaptation and virulence of Listeria monocytogenes. The growth of the L. monocytogenes parent strain 10403S and 15 isogenic alternative σ factor mutants was assessed in defined minimal medium (DM) with PTS-dependent or non-PTS-dependent carbon sources at 25°C or 37°C. Overall, our results suggested that the regulatory effect of alternative σ factors on the growth of L. monocytogenes is dependent on the temperature and the carbon source. One-way analysis of variance (one-way ANOVA) showed that the factor “strain” had a significant effect on the maximum growth rate (μ(max)), lag phase duration (λ), and maximum optical density (OD(max)) in PTS-dependent carbon sources (P < 0.05) but not in a non-PTS-dependent carbon source. Also, the OD(max) was not affected by strain for any of the three PTS-dependent carbon sources at 25°C but was affected by strain at 37°C. Monitoring by quantitative real-time PCR (qRT-PCR) showed that transcript levels for lmo0027, a glucose-glucoside PTS permease (PTS(Glc)-1)-encoding gene, were higher in the absence of σ(L), and lower in the absence of σ(H), than in the parent strain. Our data thus indicate that σ(L) negatively regulates lmo0027 and that the increased μ(max) observed for the ΔsigL strain in DM with glucose may be associated with increased expression of PTS(Glc)-1 encoded by lmo0027. Our findings suggest that σ(H) and σ(L) mediate the PTS-dependent growth of L. monocytogenes through complex transcriptional regulations and fine-tuning of the expression of specific pts genes, including lmo0027. Our findings also reveal a more important and complex role of alternative σ factors in the regulation of growth in different sugar sources than previously assumed.